Науково-методичні засади управління продуктивністю праці - Семикіна, М. В. (ЧДІЕУ, 2010)
В статті доведено необхідність вдосконалення існуючих науково-методичних засад управління продуктивністю праці та її оцінювання на різних економічних рівнях. Проаналізовано ключові проблеми управління продуктивністю праці в умовах формування конкурентного середовища, запропоновано напрями його вдосконалення в Україні. Зосереджено увагу на використанні потенціалу соціального партнерства в питаннях управління продуктивністю праці. The necessity of the perfection of the existing scientific-methodical principles of the labour productivity management and of the it's evaluation at the different eco-nomic leves has been proved in the article. The key problems of the labour productivity management in the conditions of the formation of the competitive environment have been analysed, the directions of it's perfection have been suggested. The attention has been concentrated on the use of the potential of the social partnership in the questions of the labour productivity management.
Keywords: продуктивність праці; чинники впливу; методи оцінки; соціальне партнерство; labour productivity; factors of influence; methods of estimation; mechanism; social partnership